Feeding Value of Lupins, Field Peas, Faba Beans and Chickpeas for Poultry: An Overview - David LS; Nalle CL; Abdollahi MR; Ravindran V (MDPI (Basel, Switzerland), 2024)
Grain legumes are fair sources of protein, amino acids and energy, and can be used as a replacement for soybean meal in poultry feed formulations as the soybean meal becomes short in supply and costly. However, a concern associated with the use of grain legumes in poultry feeding is the presence of antinutritional factors. The effective processing and utilisation of these grain legumes in poultry feeding are well documented. The current review focuses on four selected grain legumes (lupins [Lupinus albus and Lupinus angustifolius], field peas [Phaseolus vulgaris], faba beans [Vicia faba] and chickpeas [Cicer arietinum]) and their nutrient content, the presence of antinutritional factors, processing methods and feeding value, including updated data based on recent research findings.
Keywords: antinutrients; feed processing; feeding value; grain legumes